ILMU PENGETAHUAN (Sains), TEKNOLOGI (IPTEK), DAN KETERPADUANNYA PADA EKONOMI ISLAM - Imam, Drs. (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
Islamic economy today has grown by leaps and bounds. It can be seen from the rise of economic institutions both business and finance who carry out their business on the basis of Islamic law. Some of these institutions include Islamic banks, Islamic insurance, hotel sharia.